Social Engineering Attacks in US Healthcare: A Critical Analysis of Vulnerabilities and Mitigation Strategies (International Journal of Scientific Research and Management (IJSRM), 2022)
Social engineering attacks are increasingly becoming a serious threat to the US healthcare sector. These attacks exploit human psychology to manipulate individuals into disclosing sensitive information or performing actions that compromise security, rather than targeting technical vulnerabilities alone (Hadnagy, 2018). Given the vast amounts of personal and medical data managed by healthcare organizations, they present an attractive target for such attacks, making it crucial to understand and address these threats comprehensively (Smith & Lee, 2021). This study investigates social engineering attacks in the US healthcare system by analyzing the key vulnerabilities and evaluating the effectiveness of existing mitigation strategies. Through an extensive review of recent literature and detailed case studies, such as the 2020 ransomware attack on a major hospital network and the 2021 phishing campaign affecting multiple healthcare facilities, the research identifies common attack methods, including phishing, pretexting, baiting, and tailgating, and assesses their specific impacts on healthcare operations (Mitnick & Simon, 2011; Jones et al., 2022). The research employs a qualitative approach, including the analysis of documented attack patterns and interviews with cybersecurity experts, to evaluate the current state of security measures and identify gaps (Creswell & Poth, 2018). This approach provides a nuanced understanding of how social engineering tactics are employed and the particular vulnerabilities they exploit within healthcare settings. The findings reveal that while some healthcare organizations have adopted advanced security technologies and training programs, significant vulnerabilities persist due to outdated systems, insufficient employee training, and inadequate incident response protocols (Williams & Green, 2021). Based on these insights, the paper proposes several recommendations to enhance cybersecurity in healthcare. Key suggestions include implementing comprehensive employee training programs focused on social engineering threats, investing in advanced technologies like multi-factor authentication and intrusion detection systems, and developing robust incident response plans (Doe & Smith, 2021). These measures are essential for improving resilience against social engineering attacks, protecting sensitive patient information, and ensuring the continuity of healthcare services (Kark, 2020). By addressing these vulnerabilities and strengthening defensive strategies, healthcare organizations can better safeguard against the evolving threats posed by social engineering attacks. This research adds valuable perspectives to the ongoing discussions about cybersecurity in healthcare and offers practical guidance for enhancing defenses against these pervasive threats.